(untitled) (International journal of medical sciences, 2025)
The article covers a problem of a fatty embolism as a heavy complication of a mechanical trauma that often can be cause of death of the victim or playing a fundamental role in a thanatogenesis. The article briefly clears up the questions of an etiology and pathogenesis, clinical diagnostics and generally touches on an issue of morphological (primary – microscopic) diagnosis of a fatty embolism.